2021
DOI: 10.1111/jfbc.13950
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of apigenin as a potent antioxidant with emphasis on bioavailability, metabolism, action mechanism and in vitro and in vivo studies: A review

Abstract: Several chronic diseases like cancer, diabetes, stroke, neurodegenerative disorders, etc. are rising globally at a faster rate basically due to the increasing free radicals overproduction and oxidative stress from current lifestyle, but can be suppressed or inhibited by antioxidant compounds (Chaturvedi & Beal, 2013;Halliwell, 2012). Now-a-days, the natural antioxidants have a higher demand than the synthetic ones (Kashyap et al., 2017). Among them, flavonoids have a higher value due to their role in human hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 163 publications
3
42
0
Order By: Relevance
“…Its ability to act as a metal chelator, free radical scavenger, and regulator of the main pathways involved in redox homeostasis [i.e., Nrf2, NF-kB, MAPK (mitogen-activated protein kinase) and Akt (a.k.a. protein kinase B] has increased its interest as an antioxidant molecule [ 305 ]. For example, creams rich in apigenin are used for their beneficial effects on skin aging prevention [ 306 , 307 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its ability to act as a metal chelator, free radical scavenger, and regulator of the main pathways involved in redox homeostasis [i.e., Nrf2, NF-kB, MAPK (mitogen-activated protein kinase) and Akt (a.k.a. protein kinase B] has increased its interest as an antioxidant molecule [ 305 ]. For example, creams rich in apigenin are used for their beneficial effects on skin aging prevention [ 306 , 307 ].…”
Section: Resultsmentioning
confidence: 99%
“…Apigenin is a natural bioflavonoid present in various vegetables, herbs, spices, and fruits, and particularly in Citrus × aurantium L. (grapefruit) ( Kashyap et al, 2021 ). Apigenin can improve and ameliorate HFD-induced NAFLD syndrome in a mouse model by decreasing inflammation and hepatic lipid accumulation.…”
Section: Pharmacological Agents Associated With Nlrp3 Inflammasome Su...mentioning
confidence: 99%
“…In addition, luteolin showed surpassing results in DPPH • radical scavenging and FRAP assays compared with both vitamin C and BHT ( 72 ). The in vitro mechanism of apigenin against oxidative stress includes oxidative enzyme inhibition, modulation of redox signaling pathways (NF-κB, Nrf2, MAPK, and P13/Akt), reinforcement of enzymatic and non-enzymatic antioxidants, free radical scavenging, and metal chelation ( 74 ). An in vivo experiment in arterial aging mice conducted by Clayton et al ( 75 ) revealed that apigenin could increase NO bioavailability; normalize ROS, antioxidant expression, and oxidative stress; and abolish the inhibitory effect of ROS ( 75 ).…”
Section: Discussionmentioning
confidence: 99%